Influence d`une basse pression des pneumatiques sur les performances chronométrées chez des handibasketteurs - Leboeuf, A.; Binot, S.; Weissland, T. (Science & Sports, 2017)
Purpose: Determine the influence of low tyre pressure on field performance in wheelchair basketball players. Method: Seven elite wheelchair basketball players performed a 15m sprint, an agility test (Illinois Agility Test [IAT]) and a field test with stops and half-turns included (Étoile). Two different tyre pressures (5 bar-72.5 psi and 9 bar-130.5 psi) in random order were imposed and replicated in two passations. Wireless timing gates (Brower, Utah, USA) were positioned after 2.5, 5 and 15m and at the end of IAT and Étoile tests. The rolling distance was measured with a decelerate test for 3 wheelchairs with 5 and 9bar. The effect of low pressure on performance and reliability (with coefficient of variance; CV and intraclass correlation; ICC) of twice tests were tested. Results: With 5bar, sprint times for 2.5, 5, and 15m were significant longer than 9bar. In contrast, there is no difference between time performance at IAT and Étoile tests. A good reliability was found for the both passations with ICC ranged between 0.81 and 0.99 and CV less than 10% except for Étoile test. Conclusion: The rolling distances in the deceleration test were less with 5bar. Low pressure decreases sprint performance in straight line. The rolling resistances could explain these results. The slides observed on the parquet with 9bar do not allow to confirm the results of the sprint. Low reliability measured by Étoile test would be related to variations in different displacements, such as stops and half-turns. The prospects would be to confirm on a synthetic floor and with other disciplines as wheelchair rugby or tennis.